THE DEVELOPMENT OF MONOPOLY GAME FOR LEARNING MEDIA OF PHYSICAL EDUCATION, SPORT AND HEALTH TO JUNIOR HIGH SCHOOL STUDENTS IN PALU - Marhadi Marhadi (Journal Physical Education, Health and Recreation, 2022)
The purpose of this study is to produce forms of monopoly games that are suitable for the learning media of Physical Education for Junior School Students in Palu and to find out the effectiveness of monopoly games developed for Physical Education learning. This type of research is development (research-based development). The procedure used included 10 steps, Research location at SMP N 1 Palu, SMP N 12 Palu and SMP Labschool. The totaling of respondents was 72 students from three schools. The data used are, qualitative and quantitative data. The data analysis technique uses the Anova One Factor test. The research in a monopoly game model for the physical education learning of junior high school students in Palu with the development of infrastructure that includes the area of the playing field, the number of boxes and pictures. The increase in heart rate after playing monopoly is 25.41% of the maximum heart rate. The results of this game are packaged in a book and learning VCD. The conclusion of this research is that the form of monopoly game development is suitable for the learning media of Physical Education for Junior School Students. The Monopoly game model developed is also very effective for learning physical education.